2019
DOI: 10.3133/ofr20191011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chinook salmon (Oncorhynchus tshawytscha) fry survival at Lookout Point Reservoir, western Oregon, 2017

Abstract: A field study was conducted to estimate survival of fry-sized juvenile Chinook salmon (Oncorhynchus tshawytscha) in Lookout Point Reservoir, western Oregon, during 2017. The field study consisted of releasing three groups of genetically marked fish in the reservoir and monthly fish sampling. Fish were released during April 18-19 (43,950 fish), May 30-June 2 (44,145 fish), and on June 28, 2017 (3,920 fish). Reservoir sampling began in May and occurred monthly through October, consisting of 5-day events where ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The intent of the adult releases includes restoring biological contributions of salmon to the ecosystem, providing forage for native bull trout that were recently reintroduced, and supporting research on Chinook salmon prespawn mortality (Sharpe et al 2016;Myers 2017). Middle Fork Willamette River reservoirs have high growth opportunity for juvenile salmonids but contain large populations of predatory fishes and consequently juvenile mortality rates can be high (Brandt et al 2016;Kock et al 2019b). Juvenile Chinook salmon primarily pass dams during fall and winter months in the Middle Fork Willamette River when reservoir elevations are relatively low and deepwater passage routes are available at the dams, though passage mortality through these routes can be quite high (Keefer et al 2012(Keefer et al , 2013.…”
Section: Willamette River Basin Oregonmentioning
confidence: 99%
See 3 more Smart Citations
“…The intent of the adult releases includes restoring biological contributions of salmon to the ecosystem, providing forage for native bull trout that were recently reintroduced, and supporting research on Chinook salmon prespawn mortality (Sharpe et al 2016;Myers 2017). Middle Fork Willamette River reservoirs have high growth opportunity for juvenile salmonids but contain large populations of predatory fishes and consequently juvenile mortality rates can be high (Brandt et al 2016;Kock et al 2019b). Juvenile Chinook salmon primarily pass dams during fall and winter months in the Middle Fork Willamette River when reservoir elevations are relatively low and deepwater passage routes are available at the dams, though passage mortality through these routes can be quite high (Keefer et al 2012(Keefer et al , 2013.…”
Section: Willamette River Basin Oregonmentioning
confidence: 99%
“…Head-of-reservoir collection ( Fig. 1) is currently being considered at several sites where in-reservoir conditions are thought to limit the number of juvenile outmigrants that survive, move downstream, and enter a dam forebay for potential collection (Liedtke et al 2010;Clancey et al 2017;Kock et al 2019b). Headof-reservoir systems may be effective in reservoirs that are very large, have complex bathymetry or hydrology, or lack velocity cues needed for juvenile salmonids to successfully orient and move downstream (e.g., Shasta Reservoir on the Sacramento River, California; Clancey et al 2017).…”
Section: Fish Traps and Collection Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kock et al [10] reported considerable variation in the effectiveness of the programs reviewed, but also noted that success is context-dependent and defined by different management objectives of stakeholders. Limitations to success of reintroduction into reservoirs are varied [10] and can include migration delays and handling stress leading to high mortality rates for adults, differences in stock-specific production rates of the donor populations [11], the differential fitness of hatchery fish and impacts of interbreeding [12,13], high juvenile mortality rates associated with predation in reservoirs [14], and other challenges for downstream migrating juveniles (e.g., mismatch between water operations and migration timing, collection efficiency of smolt traps, handling stress during collection) [15,16].…”
Section: Introductionmentioning
confidence: 99%